KAJIAN ETNOMATEMATIKA PADA KAIN ADAT NAGEKEO - Coo Bule, Modesta Venidora (Lembaga PKBM Tunas Harapan Varoso, 2024)
The current educational curriculum demands cultural involvement in the learning process in schools with the aim of ensuring that students can become a generation capable of maintaining and preserving culture as the basis of national character. The study of mathematics in culture is called ethnomathematics. By applying ethnomathematics in learning, it is very possible that the material studied is related to culture and students' understanding of the material becomes easier because the material is directly related to culture which is their daily activity in society. This research aims to identify the ethnomathematics content in Nagekeo traditional cloth on flat geometric materials. This research uses qualitative methods with an ethnographic approach. The data collection techniques used are observation and documentation. Documentation is obtained when carrying out observation activities. The results of the research show that the mathematical concepts contained in Nagekeo traditional cloth resemble the concept of flat shapes, namely rhombuses, rectangles and hexagons. The ethnomathematics contained in Nagekeo traditional cloth can be used to introduce mathematics through Nagekeo traditional cloth.